Persuasive Expressions in the Nature of Recommendations on the Lyrics of the Indonesian National Song and Their Use as Indonesian Language Teaching Materials in Vocational Schools - Anantama, Muharsyam Dwi; Novala, Muhamad Fajar; Hilal, Iqbal; Doloh, Mahroso (J-Simbol: Jurnal Magister Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to describe (1) the form of suggestive persuasive expressions in the lyrics of the Indonesian National Song, (2) the content of the message contained in the lyrics of the Indonesian National Song, and (3) the implementation of the form of use of suggestive persuasive expressions as Indonesian language learning material in vocational schools. . The type of research used is qualitative research. The research subject is persuasive expressions in the lyrics of National songs. The research object is in the form of words, phrases or sentences that contain persuasive expressions in the lyrics of the National Song. The data in this research are words and sentences that are persuasive expressions in the lyrics of the National song. The data source is a collection of words or phrases from the lyrics of the National song. The data collection technique used by researchers is an advanced technique in the form of note-taking techniques. Data analysis in this study used the matching method. The results of the research found that there were forms of persuasive expressions of a suggestive nature. The dominant message content in the national anthem is the struggle for the independence of the Unitary State of the Republic of Indonesia. The aim is to motivate or inflame the enthusiasm of the fighters. This form of using persuasive expressions in the Indonesian national song can be implemented as teaching material for Indonesian Language subjects in Basic Competencies (KD) by compiling reviews of messages from two books of poetry collections that are related to situations.  Penelitian ini bertujuan untuk mendeskripsikan (1) bentuk ungkapan persuasif bersifat anjuran pada lirik lagu Nasional Indonesia, (2) isi pesan yang terkandung dalam lirik lagu Nasional Indonesia, dan (3) implementasi bentuk penggunaan ungkapan persuasif bersifat anjuran sebagai materi pembelajaran Bahasa Indonesia di SMK. Jenis penelitian yang digunakan adalah penelitian kualitatif. Subjek penelitiannya yaitu ungkapan persuasif pada lirik lagu Nasional. Objek penelitian berupa kata, frase atau kalimat yang mengandung ungkapan persuasif pada lirik lagu Nasional. Data dalam penelitian ini adalah kata dan kalimat yang ungkapan persuasif pada lirik lagu Nasional Sumber data berupa himpunan kata-kata atau frasa dari lirik lagu Nasional. Teknik pengumpulan data yang digunakan peneliti adalah teknik lanjutan berupa teknik catat. Analisis data dalam penelitian ini menggunakan metode padan. Hasil penelitian menemukan bahwa terdapat bentuk ungkapan persuasif bersifat anjuran. Isi pesan yang dominan dalam lagu kebangsaan adalah perjuangan dalam memperjuangkan kemerdekaan Negara Kesatuan Republik Indonesia. Tujuannya adalah untuk memotivasi atau mengobarkan semangat para pejuang. Bentuk penggunaan ungkapan persuasif pada lagu nasional Indonesia dapat dimplementasikan sebagai materi ajar mata pelajaran Bahasa Indonesia pada Kompetensi Dasar (KD) menyusun ulasan terhadap pesan dari dua buku kumpulan puisi yang dikaitkan dengan situasi. Keywords: National song lyrics, nationalism, persuasive expressions, teaching materials